Responsibilities of Notaryas Class II Auction Officer Regarding the Deed of Auction Minute He Makes - Subrata, Nabila Djuliana Suria Subrata; Salsabila, Ainul Mardiyah; Maskanah, Ummi (Golden Ratio of Data in Summary, 2025)
Auction is a method of selling goods or services conducted through an open bidding process, which is strictly regulated in Indonesia by laws and regulations, including the Minister of Finance Regulation No. 27/PMK.06/2016. In implementing auctions, the auction minutes act is important as an authentic document that records the auction process and its result. As a public official authorized to create authentic deeds, a notary is responsible for creating the auction minutes act, including as a Class II auction official. Although holding multiple positions is not allowed, the law grants notaries the authority to serve as Class II auction officials responsible for conducting voluntary non-execution auctions and creating the Auction Minutes Act. This article examines the legal responsibilities of notaries as Class II auction officials in creating the Auction Minutes Act, encompassing administrative, civil, and criminal aspects. Errors in creating the Auction Minutes Act may lead to serious legal consequences, including administrative sanctions, civil compensation, and criminal penalties. Additionally, notaries are required to store the minutes of the auction by applicable regulations. This study uses a normative legal research method with a legislative approach, aiming to provide an understanding of the legal responsibilities of notaries as auction officials in implementing auctions in Indonesia.